Flashcard Media on Early Childhood Expressive Language Skills - Rusbiaty Rusbiaty; Hamzah Upu; Syamsuardi Syamsuardi; Wahira Wahira; Herlina Herlina (PT. Riset Press International, 2026)
Early Childhood Education (PAUD) plays a crucial role in optimizing the development of expressive language for children aged 5-6 years, a golden age where comprehensive stimulation is needed in accordance with Law No. 20 of 2003 and Permendikbud No. 137 of 2014. However, many children still experience obstacles such as passive attitudes, limited vocabulary, and a lack of confidence in speaking, which hinder their readiness to enter primary school. This study aims to describe the expressive language skills of children aged 5–6 years before and after using flashcard media in groups, and to describe the expressive language skills of children aged 5–6 years before and after using flashcard media in pairs. The study showed that, based on the Paired Sample t test, the expressive language skills of children aged 5-6 years after using flashcards with the group learning method differed significantly from before and after the implementation of learning. Based on the results of the Wilcoxon Signed-Rank test, the expressive language skills of children aged 5-6 years who used flashcards with the paired learning method differed significantly before and after the implementation of the learning. This research can be continued using a quasi-experimental design with control groups to compare the effectiveness of group versus paired flashcards against conventional approaches. In addition, longitudinal studies are needed to measure the long-term impact on elementary school readiness, as well as the integration of digital media (such as interactive applications) to adjust to the development of early childhood education technology in Indonesia in accordance with Permendikbud No. 137 of 2014.